Association of weight loss strategies with all-cause and specific-cause mortality: a prospective cohort study - Zhiquan Diao; Yilin Zhu; Wenqi Huang; Huiyan Wen; Jiaxin Li; Jiamin Qiu; Yingying Niu; Haoyu Yan; Jianfeng Zhong; Xuerui Bai; Zhitong Xu; Xiaofeng Liang; et al. (BMC, 2024)
Abstract Background The health effects of different weight loss strategies vary greatly, and the relationship between weight loss strategies, especially the combination of multiple strategies, and death is still unclear. We aimed to examine the associations of various numbers and combinations of weight loss strategies with all-cause and specific-cause mortality and to further evaluate the associations of different total weight loss volumes with mortality. Methods Using data from NHANES (1999-2018) with 48,430 participants aged 20 and above, we collected fourteen self-reported weight loss strategies and identified five clusters using latent class analysis. Cox proportional hazards models were used to examine the association between the amounts and clusters of weight loss strategies and mortality. Results During a median follow-up of 9.1 years of 48,430 participants, 7,539 deaths were recorded (including 1,941 CVDs and 1,714 cancer). Participants who adopted 2, 3-4, and ≥ 5 weight loss strategies had a lower risk of all-cause mortality, with HRs of 0.88 (95% CI, 0.81 to 0.97), 0.89 (95% CI, 0.81 to 0.96) and 0.71 (95% CI, 0.61 to 0.82). Regardless of weight loss or weight gain categories, there was a significant trend toward reduced mortality as the number of weight loss strategies increased (P trend < 0.05). Participants who adopted cluster-1 (four strategies), cluster-2 (five strategies) and cluster-3 (three strategies) had a significantly lower risk of all-cause mortality, with HRs of 0.71 (95% CI, 0.60 to 0.84), 0.70 (95% CI, 0.55 to 0.89) and 0.81 (95% CI, 0.70 to 0.94). Among them, cluster-1 and cluster-2 are both characterized by eating less food, exercising, drinking plenty of water, lowering calories and eating less fat. Conversely, cluster-4 (five strategies) and cluster-5 (four strategies) had marginally significant effects, and they both had actual higher total energy intakes. Similar associations were observed for CVDs and cancer mortality. Conclusions Employing two or more weight loss strategies was associated with a lower risk of death, even among those who gained weight. Eating less food, exercising, drinking plenty of water, lowering calories and eating less fat is a better combination of strategies. On this basis, limiting the actual intake of total energy is necessary.